RISK MANAGEMENT IN THE ORGANIZATION OF THE HOTEL AND RESTAURANT BUSINESS (Development Service Industry Management, 2024)
The article is aimed at identifying the key aspects of risk management in the organization of hotel and restaurant business, as well as analyzing the main risks and their management in the hospitality industry in times of war. The article reveals the essence of risks and the process of their management, taking into account their diversity and impact on the enterprise. Particular attention is paid to the stages of forming a risk management system at an enterprise. The article analyzes the key aspects of the risk assessment process in the overall management system and their relevance in the context of current political and economic instability. The article examines the effects of military operations on the hotel and restaurant business, in particular, their impact on the quantitative and financial performance of enterprises. The author also identifies relevant approaches to the implementation of risk management in the hotel and restaurant business in times of war. In this context, the author substantiates the importance of preventing the existing risks associated with the war and the economic situation in the country, as well as solving the tasks of crisis management to ensure the stability and success of the enterprise. The importance of taking into account both external and internal risk management factors in the event of a crisis is emphasized.
Keywords: risk management; anti-crisis measures; risk level; hotel and restaurant industry